THEORETICAL FOUNDATIONS OF THE LINGUISTIC CONCEPT - Buranova Mekkamtosh Khalikulovna (Western European Studies, 2025)
This article discusses the theoretical foundations of the concept of "concept", which is widely used in linguistics, its content and functions. The concept is considered as a connecting unit between language and thought, culture and consciousness. The article analyzes various scientific approaches to the concept - cognitive, psycholinguistic, linguocultural and philosophical interpretations. Its multifaceted essence is revealed through the definitions given to the concept by linguists
Keywords: concept; cognitive linguistics; psycholinguistics